DEGENERATE 4-WAVE MIXING IN EXCITED-STATES FORMED BY COLLISION ASSISTED TRANSITIONS - Ewart, P; Ferguson, A; Oleary, S (1981)
A degenerate four-wave mixing signal has been generated in atomic sodium vapour-argon mixtures by a laser tuned to the excited state transition 3 2P 1 2, 3 2-42D at λ568 nm. Population of the 3 2P levels is explained by excitation in the far wing of the collision broadened resonance line. The signal strength is observed to be a linear function of argon pressure up to 60 torr. Nonlinear behaviour at higher pressures is ascribed to the formation of Na*A exciplexes. © 1981.